Peningkatan Hasil Belajar IPA Melalui Media Audio Visual pada Siswa Kelas V Sekolah Dasar - Eri Urip Raharjo; Akmal Rijal (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
This research aims to find out whether audio-visual media can improve science learning outcomes for fifth grade elementary school students. The type of research used is classroom action research (PTK). Data collection techniques using observation, tests and documentation. This research consists of 2 cycles with research procedures using the Kemmis & Mc Taggart model which includes planning, implementation, observation and reflection. The results of this research indicate that there has been an increase in science learning outcomes for class V students at SDN 16 Lubuklinggau. This is shown in cycles 1 and 2 where in cycle 1 the score increased from 20% to 50% and in cycle 2 there were 19 students who completed with a percentage of 75% from 24 students. With this it can be said that audio visual media is able to improve the science learning outcomes of class V students at SD Negeri 16 Lubuklinggau.